2006
DOI: 10.1080/02713680600976552
|View full text |Cite
|
Sign up to set email alerts
|

Tear Glucose Dynamics in Diabetes Mellitus

Abstract: This study compares tear glucose dynamic differences between 121 diabetic and nondiabetic subjects after the administration of a carbohydrate load. A quantitative chromatographic analysis of tear glucose was used and the values correlated to blood glucose values. Diabetic and nondiabetic tear glucose mean values were 0.35 +/- 0.04 mmol/L and 0.16 +/- 0.03 mmol/L, respectively. Significant differences were observed among the subject groups in both the tear and capillary blood glucose values. A correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 25 publications
2
106
0
Order By: Relevance
“…Given that aqueous tear film contains approximately 7 µL of tear fluid and the average rate of tear fluid production is 1.2 µL/min at baseline 18 , collecting larger volumes of tear fluid can cause a significant amount of irritation and induce mechanical stress on the ocular surface. Studies have also shown that lower tear fluid volume collected generally results in lower median glucose concentrations and less eye irritation 12,19 . Elevated TG levels can be prolonged for up to 30 minutes, further skewing the correlation with BG 14 .…”
Section: Significance Of Tear Fluid Collection Methodsmentioning
confidence: 99%
“…Given that aqueous tear film contains approximately 7 µL of tear fluid and the average rate of tear fluid production is 1.2 µL/min at baseline 18 , collecting larger volumes of tear fluid can cause a significant amount of irritation and induce mechanical stress on the ocular surface. Studies have also shown that lower tear fluid volume collected generally results in lower median glucose concentrations and less eye irritation 12,19 . Elevated TG levels can be prolonged for up to 30 minutes, further skewing the correlation with BG 14 .…”
Section: Significance Of Tear Fluid Collection Methodsmentioning
confidence: 99%
“…Changes in tear production and composition have been associated with diabetes, including elevated glucose levels, 31 an increase in advanced glycation end product modified proteins, 32 and a reduction in reflex tearing. 33 In this study, we investigated the expression levels of IGFBP3 and IGF-1 in human tears of normal and diabetic patients in vivo and following in vitro culture of telomerase-immortalized human corneal epithelial cells in elevated glucose.…”
Section: Introductionmentioning
confidence: 99%
“…33 Other studies indicate that diabetic and nondiabetic tear glucose mean values were 6.34 ± 0.7 mg/dl and 2.9 ± 0.5 mg/dl, respectively. 34 It should be noted that the discrepancy of the correlation coefficient (r) between blood glucose and tear glucose is caused by the different tear collection methods, e.g., filter paper or microcapillary. 35 Obviously, the development of an in situ ocular glucose sensor for diabetes control is heavily limited by the following factors: (1) it takes time to collect enough tear sample, i.e., at least 10 minutes is required to collect 10 µl of tear sample by using glass capillaries; 36 (2) the concentration of the glucose in tears is lower than that in blood; 37 and (3) very few suitable devices are able to compete against commercial blood glucose testers to quantitatively measure tear glucose in a short period of time.…”
Section: -28mentioning
confidence: 99%